2014
DOI: 10.1039/c4ce01217h
|View full text |Cite
|
Sign up to set email alerts
|

Configurational and energy study of the (100) and (110) surfaces of the MgAl2O4spinel by means of quantum mechanical and empirical techniques

Abstract: This is an author version of the contribution published on: MASSARO F. R., BRUNO M., NESTOLA F. Configurational and energy study of the (100) and (110) The configurational analysis performed in this work on MgAl 2 O 4 will be useful for studying all of the minerals belonging to the family of the normal spinels (i.e, MgCr 2 O 4 ). Indeed, the initial configurations found for the (100) and (110) faces of MgAl 2 O 4 are the same for all of the normal spinels.As concerns the (100) face, we found that the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Investigating the fracture behavior of single crystal of spinel in different orientations, Stewart et al [38] found that the fracture surface energy and elastic modulus are a minimum for {100} orientation at room temperature. Recently, Massaro et al [21] systematically studied and identified the most stable structure for {100} and {110} facets in MgAl2O4 spinel. Their study, in which they performed a detailed configurational analysis of these two facets, relied primarily on empirical potentials, but results for the {100} facets were validated with hybrid DFT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the fracture behavior of single crystal of spinel in different orientations, Stewart et al [38] found that the fracture surface energy and elastic modulus are a minimum for {100} orientation at room temperature. Recently, Massaro et al [21] systematically studied and identified the most stable structure for {100} and {110} facets in MgAl2O4 spinel. Their study, in which they performed a detailed configurational analysis of these two facets, relied primarily on empirical potentials, but results for the {100} facets were validated with hybrid DFT.…”
Section: Discussionmentioning
confidence: 99%
“…Several works have been reported on the surface structures of spinels [16][17][18][19][20]. In the case of MgAl2O4 spinel, atomistic and DFT calculations were used to understand the structure and energy of low-indexed surfaces [16][17][18]21]. Regarding dopant segregation, some researchers reported grain boundary segregation of several rare earth dopants in spinel [22,23].…”
Section: +mentioning
confidence: 99%
“…The crystal faces, (hkl) A and (h′k′l′) B (Figure 2a), that are put in contact for generating the composed slab A/B/A, can show a huge number of initial surface configurations (or surface terminations); with the term initial, we mean the surface termination obtained by cutting the bulk structure without performing the optimization of the surface structure. As we demonstrated in two recent papers, 24,25 finding these configurations is a very difficult task that requires a careful analysis of both structure and symmetry of the surface. In these papers, all of the possible initial surface configurations of some crystal faces of pyrope (Mg 3 Al 2 Si 3 O 12 ) and MgAl 2 O 4 spinel were determined: as an example, 48 and 52 As concerns the interface, this means that when a composed slab is formed by two crystal faces (hkl) A and (h′k′l′) B showing m and n surface terminations, respectively, the number of possible initial interface configurations to take into accounts is m × n. In practice, this makes difficult, or impossible in some cases, the determination of the "most stable" interface structure, namely, that showing the highest adhesion energy.…”
Section: How Many Interface Structures?mentioning
confidence: 93%
“…The surface structure and processes play a key role in many of the applications of the spinel and related materials [11]. Despite intensive studies on the spinel surface [12][13][14][15][16][17][18][19][20][21][22][23][24][25], the surface structures of MgAl 2 O 4 have been challenging for many years due to the crystallographic complexities and electrical insulating property of the material. A long-standing problem is about the energetic stability of spinel surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A long-standing problem is about the energetic stability of spinel surfaces. While (1 1 1) facets are predominant on crystals of natural spinel and other spinel-type materials, the bulk-truncated (1 1 1) surfaces were theoretically predicted to have high energies [13][14][15][21][22][23]25].…”
Section: Introductionmentioning
confidence: 99%